Eileen ebook A novel. - Moshfegh, Ottessa (2015)
Now a major motion picture streaming on Hulu, starring Anne Hathaway and Thomasin McKenzie Shortlisted for the Man Booker Prize “ Eileen is a remarkable piece of writing, always dark and surprising, sometimes ugly and occasionally hilarious. Its first-person narrator is one of the strangest, most messed-up, most pathetic—and yet, in her own inimitable way, endearing—misfits I’ve encountered in fiction. Trust me, you have never read anything remotely like Eileen .” — Washington Post So here we are. My name was Eileen Dunlop. Now you know me. I was twenty-four years old then, and had a job that paid fifty-seven dollars a week as a kind of secretary at a private juvenile correctional facility for teenage boys. I think of it now as what it really was for all intents and purposes—a prison for boys. I will call it Moorehead. Delvin Moorehead was a terrible landlord I had years later, and so to use his name for such a place feels appropriate. In a week, I would run away from home and never go back. This is the story of how I disappeared. The Christmas season offers little cheer for Eileen Dunlop, an unassuming yet disturbed young woman trapped between her role as her alcoholic father’s caretaker in a home whose squalor is the talk of the neighborhood and a day job as a secretary at the boys’ prison, filled with its own quotidian horrors. Consumed by resentment and self-loathing, Eileen tempers her dreary days with perverse fantasies and dreams of escaping to the big city. In the meantime, she fills her nights and weekends with shoplifting, stalking a buff prison guard named Randy, and cleaning up her increasingly deranged father’s messes. When the bright, beautiful, and cheery Rebecca Saint John arrives on the scene as the new counselor at Moorehead, Eileen is enchanted and proves unable to resist what appears at first to be a miraculously budding friendship. In a Hitchcockian twist, her affection for Rebecca ultimately pulls her into complicity in a crime that surpasses her wildest imaginings. Played out against the snowy landscape of coastal New England in the days leading up to Christmas, young Eileen’s story is told from the gimlet-eyed perspective of the now much older narrator. Creepy, mesmerizing, and sublimely funny, in the tradition of Shirley Jackson and early Vladimir Nabokov, this powerful debut novel enthralls and shocks, and introduces one of the most original new voices in contemporary literature. Ottessa Moshfegh is also the author of My Year of Rest and Relaxation , Homesick for Another World: Stories, and McGlue .